Recreational Thematic Dominants in News TV Discourse - M. A. Gladko (Дискурс)
Introduction. This study examines the recreational thematic diversity of recreation presented in the form of the thematic dominants list. The thematic dominants are capable of organizing news discourse around themselves and transmitting significant information. Recreation is becoming an integral feature of information discourse, a tool for managing moods and public opinion. That is why the relevance of the topic is determined by the need to study text-forming tools for the implementation of recreation in the discourse. Thematic dominants of recreation are actively involved in the structural organization of the news; implement a wide range of recreational functions. The study of their linguistic implementation rules determines the scientific novelty of the research. The key tasks of the research are to identify the repertoire of thematic dominants of recreation, their functional characteristics, the specifics of participation in the construction of the news text, as well as a description of the recreation scale.Methodology and sources. The study used traditional general scientific methods, such as description and classification of linguistic material, generalization and observation, target sampling, quantitative analysis, as well as linguistic methods: discursive, descriptiveanalytical, contextual, semantic text analysis. As the material of the research, 400 textsrepresentatives of informational TV discourse, various in thematic focus and genre representation, were selected.Results and discussion. The analysis of news discourse allows us to talk about the saturation of recreational topics that broadcast information aimed at providing conditions for rest, relaxation, distraction from everyday problems and entertainment of the addressee. The study reveals macrostructural components, which are most often filled with recreational thematic dominants. It is shown that thematic dominants are unevenly located on the bipolar scale of positive – negative recreation. The extreme, average and threshold degrees of recreation have been established, and the themes that define them have been described.Conclusion. Recreational thematic dominants are aimed at shifting the focus of describing reality for the implementation of recreational functions (the formation of mental effects – distraction, experience; entertainment, interesting leisure, etc.). Their explication represents a multi-layered semiotic system (external level (multimodal resources); internal (macro- and micro-level). Between the two extreme points of recreation there are texts with different levels of recreation, and in descending order the recreational function is combined with additional, non-creative ones.